AN INVESTIGATION ON PRE-SERVICE TURKISH LANGUAGE TEACHERS’ PERCEPTIONS OF SELF ESTEEM IN TERMS OF TECHNOLOGIC PEDAGOGIC FIELD KNOWLEDGE - Fatih YILMAZ (Fırat University, 2019)
This study, aims to investigate whether pre-service Turkish Language teachers’ perceptions of self-esteem in terms of technologic pedagogic field knowledge (TPFK) show any difference with regard to gender and level of the class. The study was conducted in line with survey model and included 139 pre-service Turkish Language teachers at 1, 2, 3 and 4 classes during the 2015-2016 terms in Turkish Language Department of Gaziosmanpaşa University. The data were collected by means of “Technologic Pedagogic Field Knowledge Self Esteem Scale” (TPFKSM) originally developed by Graham vd. (2009) and later applied to Turkish context by Timur and Taşar (2011); “Personal Information Form” developed by the researchers was also used in the data collection procedure. In the conclusion of the study, the pre-service Turkish Language teachers’ levels of perception of self-esteem in terms of Technologic Pedagogic Field Knowledge were found high; there were found positive correlation on meaningful level between in all sub-dimensions. Moreover, there were found a difference in favour of males in terms of TPFK between the sub-dimensions of the scale but there were no meaningful difference in any sub-dimension of the scale in terms of the level of the class.